When the war came home the Ottomans' Great War and the devastation of an empire - Akın, Yiğit 1975- (Stanford University Pres, 2018)
From the Balkan Wars to the Great War -- From the fields to the ranks -- Filling the ranks, emptying the homes -- Feeding the army, starving the people -- In the home : wives and mothers -- On the road : deportees and refugees